STIM1 over-activation generates a multi-systemic phenotype affecting the skeletal muscle, spleen, eye, skin, bones and immune system in mice. (21st December 2018) - Silva-Rojas, Roberto; Treves, Susan; Jacobs, Hugues; Kessler, Pascal; Messaddeq, Nadia; Laporte, Jocelyn; Böhm, Johann
Abstract: Strict regulation of Ca 2+ homeostasis is essential for normal cellular physiology. Store-operated Ca 2+ entry (SOCE) is a major mechanism controlling basal Ca 2+ levels and intracellular Ca 2+ store refilling, and abnormal SOCE severely impacts on human health. Overactive SOCE results in excessive extracellular Ca 2+ entry due to dominant STIM1 or ORAI1 mutations and has been associated with tubular aggregate myopathy (TAM) and Stormorken syndrome (STRMK). Both disorders are spectra of the same disease and involve muscle weakness, myalgia and cramps, and additional multi-systemic signs including miosis, bleeding diathesis, hyposplenism, dyslexia, short stature and ichthyosis. To elucidate the physiological consequences of STIM1 over-activation, we generated a murine model harboring the most common TAM/STRMK mutation and characterized the phenotype at the histological, ultrastructural, metabolic, physiological and functional level. In accordance with the clinical picture of TAM/STRMK, the Stim1 R304W/+ mice manifested muscle weakness, thrombocytopenia, skin and eye anomalies and spleen dysfunction, as well as additional features not yet observed in patients such as abnormal bone architecture and immune system dysregulation. The murine muscles exhibited contraction and relaxation defects as well as dystrophic features, and functional investigations unraveled increased Ca 2+ influx in myotubes. In conclusion, we provide insight into the pathophysiological effect of the STIM1 R304W mutation in different cells, tissues and organs and thereby significantly contribute to a deeper understanding of the pathomechanisms underlying TAM/STRMK and other human disorders involving aberrant Ca 2+ homeostasis and affecting muscle, bones, platelets or the immune system.